Methane direct conversion to olefins, aromatics, and hydrogen over silica entrapped bimetallic MeFe-SiO2 (Me = Co, Ni, Pd, Pt) catalysts - Han, Seung Ju; Gebreyohannes, Tsegay Gebrekidan; Woo lee, Sung; Kim, Seok Ki; Kim, Hyun Woo; Shin, Jungho; Kim, Yong Tae (Molecular Catalysis, 2023)
Here, MeFe-SiO2 (Me = Co, Ni, Pd, Pt) catalysts with bimetallic sites entrapped in a highly crystalline SiO2 structure were synthesized and used for the conversion of methane to olefins, aromatics, and hydrogen (MTOAH) at 1020°C. The MeFe-SiO2 catalysts showed polymorphic forms of cristobalite, quartz, and tridymite after reaction. Among the bimetallic catalysts, 0.5Pt1.0Fe-SiO2 exhibited the highest methane conversion (10.0%) with high hydrocarbon selectivity (79.9%) at 1020°C. In C2 (ethane, ethylene, acetylene) conversion with hydrogen co-feeding at 1020°C, acetylene was identified as a major coke precursor. MTOAH with different gas hourly space velocities (GHSV) showed that the 0.5Pt1.0Fe-SiO2 catalyst exhibited higher methane conversion and aromatics selectivity than the 1.0Fe-SiO2 catalyst. Density functional theory calculations showed that the Pt-Fe3C surface is energetically favorable for methane activation and inhibits graphitic coke deposition by C2 dehydrogenation. Consequently, a modification of the entrapped Fe sites by Pt addition improved the methane conversion and hydrocarbon selectivity of the catalyst.
Keywords: Bimetallic catalysts; Bimetallics; Coke deposition; Iron/silicum catalyst; Methane conversions; Non-oxidative; Non-oxidative methane conversion; Pd Pt catalyst; Silica catalyst; ]+ catalyst; Bimetallic catalyst; Coke deposition; Iron/silica catalyst; Natural gas; Non-oxidative methane conversion